Is There Another System? - Neville-Neil, George V. (Communications of the ACM, 2024)
The article provides an answer to a question concerning whether software research and development by people will soon be replaced by the use of artificial intelligence. The answer investigates whether large language models can be used in software development as well as encouraging developers to be aware and adaptable.